Parent attitudes, family dynamics and adolescent drinking: qualitative study of the Australian parenting guidelines for adolescent alcohol use - Gilligan Conor; Kypri Kypros (BMC, 2012)
Abstract Background Parents play a critical role in their children's introduction to alcohol. A range of parenting factors have been associated with the progression to risky drinking among adolescents, and have recently formed the basis of the Australian 'Parenting Guidelines for Adolescent Alcohol Use' designed to help parents delay or reduce their adolescents' alcohol use. Methods This study aimed to explore the experiences and attitudes of parents of adolescents to gain insight into: (1) the extent to which the behaviours of parents follow the recommendations made in the guidelines; and (2) approaches to reduce hazardous drinking among adolescents. Thirty-two telephone and face-to-face interviews were conducted with parents, and the content of discussions was examined using thematic analysis. Results Parents used approaches they thought would minimise harm and promote healthy development in their children. The guidelines address key areas of concern for parents but their adherence to these approaches is low in certain areas. Many parents provided some alcohol to their adolescents and often cited the social norm of drinking among their adolescents' peers as a source of pressure to supply. Conclusions Further dissemination of the guidelines may be the first step in a public health strategy, but it is likely that parents will require support to effectively adopt the recommendations. Understanding the influences on parents' beliefs about their children's drinking and the functions of social networks in the creation of behavioural norms relating to alcohol consumption and supply may be necessary to address adolescent risky drinking.